Hospitality industry in Cyprus: the significance of intangibles - Thomas, Alison; Krambia-Kapardis, Maria; Thomas, Alison (My University, 2006)
The purpose of this research is to provide companies in the hotel and tourism industry with an alternative reporting method to the traditional financial reporting.
Keywords: Cyprus; Hotels; Intangible assets; Performance measurement (quality); Tourism